2015
DOI: 10.3390/diagnostics5020189
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Liver Disease and the Detection of Hepatocellular Carcinoma by [18F]fluorocholine PET/CT

Abstract: Positron emission tomography (PET) using the radiopharmaceutical tracer fluorine-18 fluorocholine (FCh) can elucidate tumors based on differences in choline phospholipid metabolism between tumor and surrounding tissue. The feasibility of detecting hepatocellular carcinoma (HCC) using FCh PET has been shown despite constitutively high parenchymal choline metabolism in the liver. Since HCC frequently develops in the setting of chronic liver disease, we comparatively evaluated FCh PET/CT between cirrhotic and non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…The phospholipid signatures that best discriminated HCC from non-tumor liver tissue in our study included several different species of phosphatidylcholines. PET imaging using 18 F-fluorocholine is an imaging biomarker of phosphotidylcholine synthesis that is currently used for clinical detection of HCC in some regions [43,44] It has been shown to be superior to PET imaging of glucose metabolism with 18 F-fluoro-deoxy-D-glucose (FDG) for the detection of HCC, implying that lipogenesis is more salient than glycolysis as a metabolic feature of HCC [43,45,46]. Other studies have identified lipogenic networks characterized by specific lipid metabolites as being associated with HCC progression and survival [20].…”
Section: Discussionmentioning
confidence: 99%
“…The phospholipid signatures that best discriminated HCC from non-tumor liver tissue in our study included several different species of phosphatidylcholines. PET imaging using 18 F-fluorocholine is an imaging biomarker of phosphotidylcholine synthesis that is currently used for clinical detection of HCC in some regions [43,44] It has been shown to be superior to PET imaging of glucose metabolism with 18 F-fluoro-deoxy-D-glucose (FDG) for the detection of HCC, implying that lipogenesis is more salient than glycolysis as a metabolic feature of HCC [43,45,46]. Other studies have identified lipogenic networks characterized by specific lipid metabolites as being associated with HCC progression and survival [20].…”
Section: Discussionmentioning
confidence: 99%
“…Accumulation of [ 18 F]fluorodeoxyglucose in tumors correlates with higher glucose metabolism and cell proliferation (Minn et al, 1988;Bos et al, 2002). The substantial difference in the timeframe of image acquisition between [ 18 F]fluorodeoxyglucose (60-90 minutes) and FCH (10-15 minutes) PET scan suggests that, in addition to blood flow, membrane uptake rather than metabolism can determine FCH accumulation (Talbot et al, 2010;van den Esschert et al, 2011;Kwee et al, 2015). In fact, a number of studies failed to correlate intracellular accumulation of choline or FCH with choline metabolism (Utriainen et al, 2003;Yamaguchi et al, 2005;Rommel et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, unique accumulation of the positron emission tomography (PET) tracer [ 18 F]fluoromethylcholine (FCH) enhances the sensitivity for the detection and differentiation of focal liver lesions (Talbot et al, 2006(Talbot et al, ,2010van den Esschert et al, 2011;Kwee et al, 2015). The molecular features of the varying FCH accumulation in hepatic lesions are unknown.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study is different from most previous published clinical studies on the same topic (911). Many of the previous studies are comparative in nature, between choline or fluorocholine and the commonly used FDG for PET imaging of HCC with histological correlation in some of these studies (12). What is missing in all these previous clinical investigations are cellular characterization and validation.…”
mentioning
confidence: 99%